Analisis Kemampuan Pemahaman Konsep Fisika Materi Tekanan Pada Siswa Kelas VIII C SMPN 3 Kupang - Maria Angelina Sonia; Claudia Mariska M. Maing; Maria Ursula Jawa Mukin (Program Studi Pendidikan Fisika Universitas Katolik Widya Mandira, 2023)
The study aims to determine the level of understanding of physics concepts on pressure material in class VIII C SMPN 3 Kupang students and determine the percentage of understanding of the concept of each indicator. The research data was obtained by giving tests in the form of essays totaling 15 numbers. The data were statistically analyzed, obtained the percentage of understanding of the concept of each indicator in order are interpret 81%, exemplify 66%, classify 72%, conclude 48%, summarize 50% and explain 61%. The results of this study indicate that the most dominant understanding of physics concepts is the indicator of interpreting and is in a very high category, while the least dominant indicator is the indicator of inferring and is in the sufficient category. The order of mastery based on indicators starting from the largest is the indicator of interpreting, classifying, exemplifying, explaining, summarizing, and concluding.